Transrectal and Transvaginal Catheter Drainages and Aspirations for Management of Pelvic Fluid Collections: Technique, Technical Success Rates, and Outcomes in 150 Patients - Ballard, David H. (Abdom Radiol (NY), 2019)
PURPOSE: To evaluate outcomes of image-guided transrectal/transvaginal (TR/TV) drainage for symptomatic pelvic fluid collections (SPFCs). MATERIALS AND METHODS: Single-center retrospective study of 150 consecutive patients (36 males, 114 females, average age 41 years) who underwent attempted TR/TV drainages of SPFCs during an 11-year, 5-month period. All patients presented with pain and had SPFCs with rectal or vaginal contact on preceding diagnostic CT. Routine technique included Foley catheter insertion, image-guidance with ultrasound and fluoroscopy, 18 g/20 cm Chiba needles, and Seldinger technique for catheter insertion. No anoscope or speculum was used. SPFCs causes were classified by etiology including: postoperative, 70 (47%), gynecologic, 49 (33%), and gastrointestinal, 31 (21%). Resolution of the SPFC without the need for surgical intervention, collection recurrence, and complications were assessed. Surgical management after attempted TR/TV drainage was considered a failure. RESULTS: Technical success was achieved in 172/180 procedures (TR 128/134 [95%]; TV 44/46 [96%]). TR/TV drainage successfully managed SPFCs in 141/150 patients (94% success rate) and 145/150 patients (97%) did not require surgical intervention; 4 patients with failed TR/TV drainage attempts were managed conservatively. In 5 patients requiring surgery, 4 were after technically successful TR/TV and 1 was after a failed TR attempt. Complications occurred in 4 (3%) patients: 2 bladder punctures (both resolved with medical management), 1 propagation of sepsis, and 1 hemorrhagic return from TR drainage that prompted surgical exploration. CONCLUSION: Transrectal and transvaginal drainage had high technical success rates and were successful in managing the majority (141/150; 94%) of patients with pelvic fluid collections.